2006
DOI: 10.1039/b515566e
|View full text |Cite
|
Sign up to set email alerts
|

Droplet-based microfluidics with nonaqueous solvents and solutions

Abstract: In droplet-based ("digital") microfluidics, liquid droplets in contact with dielectric surfaces are created, moved, merged and mixed by applying AC or DC potentials across electrodes patterned beneath the dielectric. We show for the first time that it is possible to manipulate droplets of organic solvents, ionic liquids, and aqueous surfactant solutions in air by these mechanisms using only modest voltages (<100 V) and frequencies (<10 kHz). The feasibility of moving any liquid can be predicted empirically fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
195
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(196 citation statements)
references
References 53 publications
1
195
0
Order By: Relevance
“…9 is always positive since the electrowetted contact angle ⎝ e is always lower than ⎝ n and both are <180 o . The sum of first two terms is negative, but for a wide range of dimensions typically used in EWOD devices and empirically observed contact angles from literature (at no applied potential [9] and at EWOD potential [10] for device geometry close to our conditions), the third term dominates. Thus, higher surface tension increases the splitting pressure, p n --p e .…”
Section: Splitting Pressure: Influence Of Liquid Properties and Geometrymentioning
confidence: 72%
See 1 more Smart Citation
“…9 is always positive since the electrowetted contact angle ⎝ e is always lower than ⎝ n and both are <180 o . The sum of first two terms is negative, but for a wide range of dimensions typically used in EWOD devices and empirically observed contact angles from literature (at no applied potential [9] and at EWOD potential [10] for device geometry close to our conditions), the third term dominates. Thus, higher surface tension increases the splitting pressure, p n --p e .…”
Section: Splitting Pressure: Influence Of Liquid Properties and Geometrymentioning
confidence: 72%
“…The specimen liquids used in this work span a wide range of properties, most importantly surface tension and density. Thus, we anticipate that the technique presented here can be extended to many other solvents and reagents used in organic chemistry, provided that they can be actuated using EWOD digital microfluidics [10].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a decrease in the driving force, and the droplet quickly comes to rest as the forces equilibrate. Solving Equation (10) shows that for a droplet volume <0.65 µL and a channel diameter of 1.1 mm, the capillary forces exceed the insertion forces ( Figure 5). Indeed, our experiments showed that with these volumes and dimensions, vertical functionality could only be obtained with hydrophilic walls.…”
Section: Characterization Of Droplet Forces and Design Parametersmentioning
confidence: 99%
“…To move the droplets, an electrical potential is applied to electrodes adjacent to the target liquid droplet. The resulting electromechanical force drives droplet translation through a combination of electrowetting and dielectrophoretic (DEP) mechanisms, depending on the liquid and the applied frequency [8,10,11]. Translation by electrowetting can be analyzed in terms of an electrostatic force, a surface tension force, and a pressure force [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relatively complex circuitry and the high sampling rates required in this measurement approach limit the applicability in low cost and point of care devices; in addition, this approach is limited to detect capacitance change when the EWOD device is being operated under DC voltage conditions. DC operation severely limits the variety of liquids that can be actuated 22 and increases the chance of dielectric breakdown in the device 23 , which may cause irreversible reactions and oxidation in the chip 24 . Furthermore, the accuracy and the resolution are fundamentally limited by the magnitude of the induced frequency shift and ability of the system to resolve high frequency modulations.…”
Section: Introductionmentioning
confidence: 99%